Zeolite-catalysed C–C bond forming reactions for biomass conversion to fuels and chemicals. Issue 8 (18th March 2016) - Resasco, Daniel E.; Wang, Bin; Crossley, Steven
Abstract : Biomass conversion to fuels requires elimination of oxygenated functionalities along with formation of C–C bonds to help keeping the largest possible amount of carbon in the fuel range ( e.g. C7–C15). Abstract : Biomass conversion to fuels requires elimination of oxygenated functionalities along with formation of C–C bonds to help keeping the largest possible amount of carbon in the fuel range ( e.g. C7–C15). Acidic zeolites are particularly effective in catalysing C–C bond forming reactions from molecules containing oxygenated functionalities such as carbonyl, carboxylic, and hydroxide groups, including acylation, ketonization, and alkylation. The nature of the active sites and possible reaction mechanisms for these reactions are discussed in this mini-review.